Two new species of rhabdochonids (Nematoda: Rhabdochonidae) from freshwater fishes in Mexico, with a description of a new genus - Caspeta-Mandujano, J M; Moravec, F; Salgado-Maldonado, G (The Journal of parasitology, 2001)
Two new nematode species, Beaninema nayaritense n. gen., n. sp. and Rhabdochona xiphophori n. sp., are described on the basis of the specimens recovered from the gall bladder and intestine of 2 fishes, Cichlasoma beani (Jordan) (Cichlidae, Perciformes) and Xiphophorus sp. (Poeciliidae, Cyprinodontiformes), respectively, from Mexico. The monotypic genus Beaninema differs from other rhabdochonid genera mainly in the presence of large conical teeth in the middle of the prostom. Rhabdochona xiphophori is characterized mainly by a unique structure of the prostom (presence of 6 anterior teeth; dorsal and ventral teeth unusually broad, with 2 lateral horns) and the shape of the deirids (bifurcated, with markedly long base).
Keywords: Perciformes; Female; Nematoda; nemoci ryb; hlístice; Animals; Mexiko; Microscopy, Electron, Scanning; ženské pohlaví; Nematode Infections; mužské pohlaví; Male; zvířata; mikroskopie elektronová rastrovací; Fish Diseases; Mexico; nematodózy